The effect of vitamin D on sarcopenia depends on the level of physical activity in older adults. Issue 3 (5th February 2020) - Yang, Aolin; Lv, Qingqing; Chen, Feng; Wang, Yingfang; Liu, Yixuan; Shi, Wanying; Liu, Ying; Wang, Difei
Abstract: Objective: Sarcopenia in older adults is closely related to vitamin D deficiency and reduced levels of physical activity, but little has been reported on the interaction between physical activity and the positive effects of vitamin D. The purpose of this study was to explore the interactive effect of vitamin D and physical activity on muscle mass and function through animal experiments and population surveys. Methods: Male 4‐week‐old C57BL/6J mice were fed different purified diets: a vitamin D‐deficient diet (with increased calcium and phosphorus to prevent the effects of abnormal mineral levels on muscle) or a 1, 25‐dihydroxyvitamin D3 (1, 25D)‐supplemented diet. After 24 weeks on the assigned diets, the mice were immobilized. The level of skeletal muscle atrophy in the mice was determined by grip strength, gastrocnemius (GA) muscle mass and muscle fiber cross‐sectional area (CSA); additionally, the protein expression levels of FOXO3a and the E3 ubiquitin ligases MuRF1 and MAFbx were detected. A cross‐sectional study included data from 4139 older adults (64.9% women, 67.9 ± 6.7 years) as part of a survey in Shenyang, Northeast China. The associations of serum 25(OH)D3 and physical activity with timed up and go test (TUG) performance, handgrip strength, calf circumference, and body muscle mass were assessed by a linear regression analysis that was adjusted for covariates. Results: In activity‐limited mice, vitamin D deficiency accelerated the decrease in GA muscle weight, muscle fiber CSA, and grip strength and increased the protein expression of MuRF1, MAFbx, and FOXO3a (all P < 0.05). In addition, 1, 25D supplementation may inhibit the grip‐strength reduction induced by limited activity ( P = 0.069). Serum 25(OH)D3 and physical activity were linearly related to TUG time ( P < 0.001) and handgrip strength ( P < 0.05) after adjustment for sex, age, body mass index (BMI), education level, smoking status, and serum calcium level. Serum 25(OH)D3 and physical activity had interactive effects on TUG ( P < 0.001) and handgrip strength ( P < 0.05) but not calf circumference or body muscle mass in older adults. Conclusions: The effect of vitamin D on muscle strength and physical performance depends on physical activity level in the elderly. It is recommended that older adults strive to avoid both physical inactivity and vitamin D deficiency. Because physical inactivity and vitamin D deficiency may exacerbate muscle atrophy, the biological mechanism may involve synergistic effects of vitamin D and physical activity on the promotion of muscle protein ubiquitination and degradation.